2007
DOI: 10.1016/j.expneurol.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclicity of spontaneous recurrent seizures in pilocarpine model of temporal lobe epilepsy in rat

Abstract: Pilocarpine administration to rats results in status epilepticus (SE) and after a latency period to the occurrence of spontaneous seizures. The model is commonly used to investigate mechanisms of epileptogenesis as well as the antiepileptic effects of novel compounds. Surprisingly, there have been no video-EEG studies determining the duration of latency period from SE to the appearance of the first spontaneous seizures or the type and frequency of spontaneous seizures at early phase of pilocarpine-induced epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
136
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 23 publications
27
136
0
4
Order By: Relevance
“…Although these seizure frequencies are only estimates of the actual seizure frequency over long time periods, they are comparable with the observations from other major laboratories using the pilocarpine model of AE: Pitkanen and co-workers have reported a frequency of 2.6 seizures per day (Goffin et al, 2007); Holmes and co-workers have reported 5.2 seizures per 42 h (Cha et al, 2004), and Dudek and coworkers have reported 6.9 seizures per day (Hernandez et al, 2002). Seizure durations are relatively short (35-50 s) in the pilocarpine model and animals have been shown to tolerate several brief seizures per day without significant behavioral effects (Goffin et al, 2007). Since the seizure frequencies observed in this study were comparable to those described by other laboratories, the observed decrease in calbindin expression presented here in the epileptic animals was not due to a high seizure frequency.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Although these seizure frequencies are only estimates of the actual seizure frequency over long time periods, they are comparable with the observations from other major laboratories using the pilocarpine model of AE: Pitkanen and co-workers have reported a frequency of 2.6 seizures per day (Goffin et al, 2007); Holmes and co-workers have reported 5.2 seizures per 42 h (Cha et al, 2004), and Dudek and coworkers have reported 6.9 seizures per day (Hernandez et al, 2002). Seizure durations are relatively short (35-50 s) in the pilocarpine model and animals have been shown to tolerate several brief seizures per day without significant behavioral effects (Goffin et al, 2007). Since the seizure frequencies observed in this study were comparable to those described by other laboratories, the observed decrease in calbindin expression presented here in the epileptic animals was not due to a high seizure frequency.…”
Section: Discussionsupporting
confidence: 84%
“…One animal demonstrated a cluster of high seizure frequencies and skewed the data to reflect a higher mean seizure frequency for this group. For long-term studies, animals were monitored two times at 12 and 24 months following SE and were found to have a mean seizure frequency of 0.9 ± 0.4 seizures per 6 h. The seizure frequencies observed in this study were comparable to those seen in other studies employing the pilocarpine model (Goffin et al, 2007;Hernandez et al, 2002;Cha et al, 2004;Wallace et al, 2003).…”
Section: Epileptogenesis Causes a Permanent Decrease In Hippocampal Csupporting
confidence: 80%
See 2 more Smart Citations
“…Evolving patterns are commonly observed in posttraumatic and poststroke epilepsy models (Pitkänen et al 2006;Kadam et al 2010), in models of mesial TLE either secondary to pharmacologically induced status epilepticus (Williams et al 2009;Bortel et al 2010;Levesque et al 2012), or induced by kindling (Michalakis et al 1998). As in humans, seizures in experimental animals with partial epilepsy occur randomly, often in clusters (Grabenstatter et al 2005;Goffin et al 2007;Williams et al 2009). In in vitro preparations (brain slices and in toto preparations) isolated from chronically epileptic animals, interictal activity can be seen, but seizures do not occur spontaneously and are usually evoked by either pharmacological manipulations or patterned stimulations.…”
Section: Seizure Patternsmentioning
confidence: 99%